RELATIONSHIPS WITH TAX AUTHORITIES AS A DETERMINANT OF TAX CONSULTANT PERFORMANCE IN INDONESIA - Sitawati, Riana; Christina, Oei Kezia (Jurnal Akuntansi dan Keuangan Indonesia, 2025)
Background: Tax consultants are central to supporting taxpayer compliance in Indonesia. While technical competence is essential, their performance also depends on constructive engagement with tax authorities, an aspect rarely examined in the Indonesian context. Methods: This study employed a quantitative survey of 158 licensed tax consultants in Indonesia. Data were analyzed using Structural Equation Modeling (SEM-PLS) to test the direct and mediating effects of technical skills and relationships with tax authorities on job performance. Findings: The results indicate that technical skills significantly improve both relationships with tax authorities and perceived job performance. Furthermore, relationships with tax authorities mediate the effect of technical skills on performance, highlighting their strategic role in enhancing consultants’ effectiveness. Conclusion: Strong technical competence, when combined with positive relationships with tax authorities, enables consultants to provide accurate advice, strengthen compliance, and build professional credibility. For policymakers and professional associations, these findings suggest the importance of continuous technical training and fostering collaborative forums between tax consultants and tax authorities. Novelty/Originality: This study contributes empirical evidence from Indonesia by introducing relationships with tax authorities as a mediating variable between technical skills and tax consultant performance. This relational perspective enriches existing tax compliance literature and offers insights for professional practice.